A thousand ships : a novel - Haynes, Natalie (Harper, an imprint of HarperCollinsPublishers, 2021)
A retelling of the Trojan War from the perspectives of its women follows the stories of a vigil-keeping Penelope, an Amazon princess rival of Achilles, and three goddesses whose feud sparks a tragic conflict.